2004
DOI: 10.1097/01.ju.0000108842.27907.47
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor Thrombus Level in Patients With Renal Cell Carcinoma and Venous Tumor Thrombus Extension. Is All T3b the Same?

Abstract: The level of tumor thrombus in the IVC does not significantly effect long-term survival. Ten-year survival of patients classified as T3b is statistically different for patients having tumor thrombus in the renal vein compared to level I. Combining these 2 groups as T3b by the 1997 TNM staging may need to be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
2
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(119 citation statements)
references
References 13 publications
11
89
2
17
Order By: Relevance
“…98 In subsequent studies conflicting results as to the prognostic significance of this classification have been reported, with some studies validating the classification, [99][100] whereas others have shown that the level of tumor thrombus beyond the renal vein does not influence survival. [101][102][103][104][105] To predict the outcome more accurately in locally advanced disease, additional parameters have been proposed to further stratify tumors showing vascular invasion. In particular, the poor prognosis associated with perirenal fat, adrenal and Gerota's fascia infiltration has led to the incorporation of those features into a proposed modification of pT3-4 criteria.…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…98 In subsequent studies conflicting results as to the prognostic significance of this classification have been reported, with some studies validating the classification, [99][100] whereas others have shown that the level of tumor thrombus beyond the renal vein does not influence survival. [101][102][103][104][105] To predict the outcome more accurately in locally advanced disease, additional parameters have been proposed to further stratify tumors showing vascular invasion. In particular, the poor prognosis associated with perirenal fat, adrenal and Gerota's fascia infiltration has led to the incorporation of those features into a proposed modification of pT3-4 criteria.…”
Section: Regional Spread Of Tumor (Tnm Category T3)mentioning
confidence: 99%
“…Therefore, detailed preoperative staging is necessary for proper surgical planning [13]. A survival rate of patients with RCC depends on local tumor expansion, as well as the level of venous involvement and the presence of distant metastases [14,15].…”
mentioning
confidence: 99%
“…[5][6][7] Moreover, controversy exists regarding the prognostic significance of the cranial extension of venous tumor thrombus (VTT), the location of extrarenal extension (ERE), and the concomitant presence of both pathologic features. [8][9][10][11][12][13] By examining the prognostic features and cancerspecific outcomes of a large cohort of patients treated within the past 15 years for RCC at a tertiary referral center, this study seeks to reassess and suggest possible improvements to the 2002 AJCC pT3 classification of RCC.…”
Section: Resultsmentioning
confidence: 99%